Identification of off-patent drugs that show synergism with amphotericin B or that present antifungal action against Cryptococcus neoformans and Candida spp. - Rossi, Suélen Andreia; De Oliveira, Haroldo Cesar [UNESP]; Agreda-Mellon, Daniel; Lucio, José; Soares Mendes-Giannini, Maria José [UNESP]; García-Cambero, Jesús Pablo; Zaragoza, Oscar (American Society for Microbiology, 2020)
Amphotericin B (AmB) is the antifungal with the strongest fungicidal activity, but its use has several limitations, mainly associated with its toxicity. Although some lipidic and liposomal formulations that present reduced toxicity are available, their price limits their application in developing countries. Flucytosine (5FC) has shown synergistic effect with AmB for treatment of some fungal infections, such as cryptococcosis, but again, its price is a limitation for its use in many regions. In the present work, we aimed to identify new drugs that have a minor effect on Cryptococcus neoformans, reducing its growth in the presence of subinhibitory concentrations of AmB. In the initial screening, we found fourteen drugs that had this pattern. Later, checkerboard assays of selected compounds, such as erythromycin, riluzole, nortriptyline, chenodiol, nisoldipine, promazine, chlorcyclizine, cloperastine, and glimepiride, were performed and all of them confirmed for their synergistic effect (fractional inhibitory concentration index [FICI] < 0.5). Additionally, toxicity of these drugs in combination with AmB was tested in mammalian cells and in zebrafish embryos. Harmless compounds, such as the antibiotic erythromycin, were found to have synergic activity with AmB, not only against C. neoformans but also against some Candida spp., in particular against Candida albicans. In parallel, we identified drugs that had antifungal activity against C. neoformans and found 43 drugs that completely inhibited the growth of this fungus, such as ciclopirox and auranofin. Our results expand our knowledge about antifungal compounds and open new perspectives in the treatment of invasive mycosis based on repurposing off-patent drugs.
Keywords: Amphotericin B; Candida; Cryptococcus neoformans; Drug repurposing; Synergism